Exploring Brand Voice Through Chatbot Interactions in Indonesian Low-Cost Airlines - Devita Auliana Putri; Nella Atikah (Journal of Communication and Public Relations, 2026)
In the digital era, artificial intelligence (AI) has become an influential tool in brand voice, especially within the airline industry. Indonesian low-cost carriers (LCCs) such as Lion Air, Citilink, and AirAsia Indonesia are increasingly integrating AI-powered chatbots into their customer service operations to enhance efficiency and shape brand perception. Despite the growing adoption of this technology, there remains limited academic focus on how chatbots contribute to brand voice  in the context of Indonesian LCCs. This study aims to explore how these three major LCCs utilize AI-driven chatbots to project brand identity and values. Using a qualitative descriptive method, the research applies thematic analysis to simulated chatbot-user interactions based on common service scenarios, such as ticket inquiries, baggage policies, rescheduling, and complaint handling. These conversations, gathered from each airline’s official digital platform, are transcribed and analyzed using a six-phase framework. The analysis pays close attention to communicative elements such as language style, tone of voice, word choice, and use of visual symbols like emojis which are interpreted as indicators of each brand's voice and persona. The study is expected to reveal distinctive communication patterns across the three airlines, offering insights into how each brand strategically constructs its voice, whether warm and friendly, efficient and concise, casual, or professional. Beyond contributing to academic discussions on AI-mediated brand voice, the findings provide practical implications for communication practitioners, digital developers, and policymakers. By grounding the analysis in real-world data and a localized industry context, this research highlights the strategic potential of chatbots not just as service tools, but as integral elements of digital brand storytelling in Southeast Asia’s growing aviation market.